Impact of @RaikuBeauty instagram campaign content on brand image - Octaviana, Vanisha; Susilo, Daniel (Fakultas Ilmu Komunikasi Universitas dr. Soetomo, 2021)
Most Indonesian women often feel insecure about their appearance without makeup. Raiku Beauty is here as one of the new beauty brands that motivates Indonesian women to be able to appear confident by taking care of their skin using skincare from Raiku. The purpose of this study was to determine whether the content on Instagram @RaikuBeauty related to the â€œDare to be Bareâ€ campaign was able to have a significant influence on the brand image. The theory used in this study is the content of communication messages on social media. This research is quantitative explanative with data collected through a survey to 395 respondents obtained from the Taro Yamane formula. The data obtained were then tested for hypotheses with simple linear regression. The results showed that there was a significant impact of social media content on the dare to be bare campaign on brand image, with 60.2% degree of impact. Keywords: social media content; brand image; instagram; raiku beauty.